2021
DOI: 10.3389/fchem.2021.744417
|View full text |Cite
|
Sign up to set email alerts
|

Li-Rich Antiperovskite/Nitrile Butadiene Rubber Composite Electrolyte for Sheet-Type Solid-State Lithium Metal Battery

Abstract: Lithium-rich antiperovskites (LiRAPs) hold great promise to be the choice of solid-state electrolytes (SSEs) owing to their high ionic conductivity, low activation energy, and low cost. However, processing sheet-type solid-state Li metal batteries (SSLiB) with LiRAPs remains challenging due to the lack of robust techniques for battery processing. Herein, we propose a scalable slurry-based procedure to prepare a flexible composite electrolyte (CPE), in which LiRAP (e.g., Li2OHCl0.5Br0.5, LOCB) and nitrile butad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…It is reported that the mass loss during the high‐temperature solid reaction is less than 1%. [ 33 ] Therefore, it is easy to tune the H amount in the LiRAPs by replacing a part of LiOH with Li 2 O. O–H vibration mode features a shoulder peak positioned at 3660 cm −1 in FTIR spectrum, [ 17 ] as shown in Figure 1c. As the H amount decreases, the intensity of the shoulder peak is gradually weakened.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is reported that the mass loss during the high‐temperature solid reaction is less than 1%. [ 33 ] Therefore, it is easy to tune the H amount in the LiRAPs by replacing a part of LiOH with Li 2 O. O–H vibration mode features a shoulder peak positioned at 3660 cm −1 in FTIR spectrum, [ 17 ] as shown in Figure 1c. As the H amount decreases, the intensity of the shoulder peak is gradually weakened.…”
Section: Resultsmentioning
confidence: 99%
“…By replacing the flammable liquid electrolyte with nonflammable solid electrolytes (SEs), all‐solid‐state Li metal batteries (ASSLMBs) are considered as safer alternatives for energy storage compared with the commercial Li‐ion batteries. [ 1–13 ] Among the reported families of SEs, Li‐rich antiperovskite (LiRAP) SEs (e.g., Li 3 OCl) possess the advantages of high Li ion conductivity (10 −3 S cm −1 ), low activation energy (<0.3 eV), wide electrochemical window, light weight, low cost, and low toxicity, [ 14–21 ] which show great promises for practical applications. They have a similar crystal structure to the conventional perovskites but with electronically inverted lattice sites.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations